Ayah Asi dalam Perspektif Al-Qur'an - Mohamad Shofin Sugito (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2017)
The Article describes about the breastfeeding and its significance for the baby and making more powerful relationship in a family. It is caused by the good cooperation between father and mother to get the roles of each others. Especially, the article presents the perspective of Al-Qur’an about the breastfeeding and the mother role, and the discuss deeply the breastfeeding father according to Qur’anic scholars, as fundamental theology doctrine. Thus, the article aims to highlight, explain and discuss the breastfeeding as true baby’s right and it becomes the responsibility of his father-mother. The method here is using literature reviews from classical and contemporary Islamic books, related to the Qur’anic interpretation, the breastfeeding and its functions, and the roles of father in activity of breastfeeding. It gives the new horizan of thinking about participation and cooperation between father and mother in modern society life.